Efesiensi Fisik Komputer Server dengan Menerapkan Proxmox Virtual Environment - Saidi Ramadan Siregar (Journal of Computer System and Informatics (JoSYC), 2020)
Along with the development of desktop and non desktop application software, the provision of services to accommodate requests from client computers is increasing too, which can be seen in terms of usage environment whether in local or public network coverage. for example an information system program created using the Microsoft visual studio.Net application by using database access, the server computer even though it uses a Windows operating system, and vice versa if the information system program that is built using a web programming language (opensource) is mostly among programmers choosing to use a web server with linux operating system. To do this, the network manager creates a solution so that the information system that is built from any programming language can be run on one physical computer server with a virtualization system by applying the Proxmox virtual environment as a virtual machine container that will accommodate several types of operating systems.